2008
DOI: 10.1002/cssc.200800133
|View full text |Cite
|
Sign up to set email alerts
|

Breakthroughs in Hydrogen Storage—Formic Acid as a Sustainable Storage Material for Hydrogen

Abstract: A boost for fuel cells: Recent results suggest that formic acid is a convenient hydrogen‐storage material: its decomposition yields CO‐free hydrogen while the co‐produced carbon dioxide can be hydrogenated back to formic acid. The hydrogen generated in this way is suitable for fuel cell applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
155
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 505 publications
(157 citation statements)
references
References 28 publications
1
155
1
Order By: Relevance
“…[1][2][3][4] In this context, one of the most significant challenges of hydrogenbased energy generation is the storage of large quantities of hydrogen at safe pressures. [1] In particular for portable applications, the use of liquid hydrogen has several disadvantages due to its continuous evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In this context, one of the most significant challenges of hydrogenbased energy generation is the storage of large quantities of hydrogen at safe pressures. [1] In particular for portable applications, the use of liquid hydrogen has several disadvantages due to its continuous evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recent studies have shown that HCOOH decomposition is catalyzed with Ru-based complexes in the aqueous phase at near-ambient temperatures. [5,6] HCOOH decomposition reactions are used frequently to probe the effects of alloying and cluster size and of geometric and electronic factors in catalysis [7][8][9][10] .…”
mentioning
confidence: 99%
“…Due to the rather low volumetric energy density of hydrogen, methods for its incorporation into materials, as well as its temporary introduction into carrier molecules, are under intensive investigation [67,68]. Within this context, formic acid is one possibility of transiently storing H 2 [69]. In order to use molecular hydrogen as a green fuel, efficient catalytic liberation from the storage materials is an important prerequisite for this technology.…”
Section: Use Of [(Bpy)rh(cp*)x] N+ Catalysts For Hydrogen Evolution Amentioning
confidence: 99%